They have taken out my spinal cord: an interpretative phenomenological analysis of self-boundary in psychotic experience within a sociocentric culture - Alphonsus, Elizabeth; Fellin, Lisa C.; Thoma, Samuel; Galbusera, Laura (Frontiers in Psychiatry, 2023)
Introduction: In the tradition of phenomenological psychiatry, schizophrenia is described as a disturbance of the minimal self, i.e. the most basic form of self-awareness. This disturbance of the minimal self at the individual level is assumed to precede the intersubjective disturbances such as boundary weakening. However, the role of intersubjective disturbances in the emergence and recovery of schizophrenic experience still remains an open question. This phenomenological study focuses on how encounters with others shape self-experience during from psychosis by analysing this process from the perspective of cultural differences, which in current research is especially under-researched. While most phenomenological accounts are based on first person-accounts from Western, individualist cultures where the self is conceived and experienced as separate to others, the present study qualitatively investigates psychotic experiences of patients from Jaffna, Sri Lanka. Method: Semi-structured interviews were conducted with three participants with a diagnosis of schizophrenia or first episode psychosis. The interviews were transcribed and analysed using interpretative phenomenological analysis (IPA). Eight group experiential themes were identified across interviews (Smith, Flowers, & Larkin, 2021). Results: The data suggest that intersubjective processes of boundary weakening such as invasiveness and hyperattunement may shape minimal self-experience and more specifically contribute to a mistrust of the own senses and to hyper-reflexivity. Interestingly, boundary weakening yields pervasive emotions and can be experienced as a threat to the whole social unit. On the one hand, the strengthening of self-other-boundary was achieved through opposition, closedness and withdrawal from others. On the other hand, this study suggests that the re-opening of self-other-boundaries in response to the crisis may help establish connectedness and may lead to recovery.